1996
DOI: 10.1074/jbc.271.47.30077
|View full text |Cite
|
Sign up to set email alerts
|

Threonine 1342 in Human Topoisomerase IIα Is Phosphorylated Throughout the Cell Cycle

Abstract: To investigate the relationship between the modulation of topoisomerase II activity and its phosphorylation state during the cell cycle, a monoclonal antibody against C-terminal peptide (residues 1335-1350) of topoisomerase II␣ containing a consensus sequence of casein kinase II, TDDE and its phosphorylated threonine were prepared. In an enzyme-linked immunosorbent assay, the antibody, named PT1342, recognized the immunogenic phosphopeptide but not the non-phosphorylated form of the peptide. The PT1342 antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 56 publications
(53 reference statements)
1
43
0
1
Order By: Relevance
“…In these yeast, topoisomerase II is hypo-phosphorylated and inactive, suggesting that it is a bona fide physiological target for CK2. Additionally, it was recently demonstrated in mammalian cells that CK2 phosphorylates residues on topoisomerase II␣, including Thr-1342, which are residues that are maximally phosphorylated in mitotic cells (32)(33)(34). In this study, we demonstrated that Pin1 inhibits the in vitro phosphorylation of Thr-1342 on topoisomerase II␣ by CK2 and that Pin1 interacts with topoisomerase II␣.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…In these yeast, topoisomerase II is hypo-phosphorylated and inactive, suggesting that it is a bona fide physiological target for CK2. Additionally, it was recently demonstrated in mammalian cells that CK2 phosphorylates residues on topoisomerase II␣, including Thr-1342, which are residues that are maximally phosphorylated in mitotic cells (32)(33)(34). In this study, we demonstrated that Pin1 inhibits the in vitro phosphorylation of Thr-1342 on topoisomerase II␣ by CK2 and that Pin1 interacts with topoisomerase II␣.…”
mentioning
confidence: 59%
“…Incorporation of 32 P into Topoisomerase II-The wild-type Y2C fragment of topoisomerase II␣ and the mutant form with the Thr-1342 to alanine substitution T1342A were produced in bacteria and then purified and blotted to polyvinylidene difluoride membrane as described above (33). The membranes were blocked in 5% BSA in TBST.…”
Section: Y23amentioning
confidence: 99%
See 2 more Smart Citations
“…Residue numbers are taken from Medline files. A third phosphorylation site has been described for Thr-1343 (44). Recent studies report that the MPM-2 epitope on topoisomerase II␣ is present on Thr-666 whereas the 3F3/2 epitope corresponds to Thr-1343 (15,45).…”
Section: Ck2 Creates a Limited Number Of Mpm-2 Reactive Bands In Totamentioning
confidence: 99%